Public Policies and the Employment of Mothers: A Cross-National Study - Janet C. Gornick; Marcia K. Meyers; Katherin E. Ross (Luxembourg Income Study (LIS), 1996)
This paper uses data from fourteen industrialized countries, during the middle to late 1980's, to analyze the effect of national child care and maternity leave policies on employment. The results demonstrate a strong association between policy configurations and the employment patterns of women with children.
Keywords: 330; Weibliche Arbeitskräfte; Mütter; Mutterschutz; Kinderbetreuung; Industrieländer